PENGARUH PEMURNIAN DEGUMMING DAN NETRALISASI TERHADAP PROFIL MINYAK BIJI LABU KUNING (Cucurbita moschata D.) - Hartati Soetjipto; Apriyanti Tindage; Margareta Novian Cahyanti (JURNAL KONVERSI, 2018)
ABSTRACTThe objective of the study were to obtain of pumpkin (C. moschata D.) seed oil yield using hexane soxhlet extraction method and the effect of purification on the profile of pumpkin seed oil fatty acids. The results of the study showed that the yield of pumpkin seed crude oil was 37,98% (b/b), whereas the optimum rendement after purification was 76,27% (w/w) by using 0,15% H3PO4. The GC-MS analysis of pumpkin seed oil showed the presence of three same main components of pumpkin seed oil before and after purification which are: linoleic acid, palmitic acid, and stearic acid, respectively. The content of pumpkin seed oil before purification are as follows: 57,96% of linoleic acid, 24,63% of palmitic acid, dan 6,82% of stearic acid, respectively. In the contrary, the content of pumpkin seed oil after purification are as follows: 48,21% of linoleic acid, 20,70% of palmitic acid, dan 5,27% stearic acid, respectively. The purification processes do not affect on the main components of pumpkin seed oil, but determine the difference percentages of pumpkin seed oil main components.